Sperm fractions obtained following density gradient centrifugation in human ejaculates show differences in sperm DNA longevity - Jaime Gosálvez; Stephen Johnston; Carmen López-Fernández; Altea Gosálbez; Francisca Arroyo; Jose Luís Fernández; Juan GÁlvarez (Asian Pacific Journal of Reproduction, 2014)
Objective: To investigate the DNA longevity characteristics associated with each resultant fraction following density gradient centrifugation (DGC) in comparison to that of the original neat ejaculated sample. Methods: An aliquot of neat semen (NSS) collected from 7 patients was processed using DGC resulting in 3 fractions; Fraction 1: seminal plasma/40% gradient interface (GI); Fraction 2: 40%GI/80%GI; Fraction 3: 80%GI/pellet. An aliquot of each fraction and NSS was cryopreserved, thawed and incubated at 37 ° for 24h; the increase of sperm DNA fragmentation was assessed using the Dyn-Halosperm assay following 0, 3, 6 and 24h of incubation. Results: While there was a significant reduction in the incidence of baseline sperm DNA fragmentation following DGC in Fraction 3, sperm DNA longevity was shown to be higher in the NSS than in any other sub-population following incubation. The highest levels of baseline DNA damage were found in Fractions 1 and 2; these fractions also showed the highest rate DNA fragmentation following incubation, subsequently exhibiting the lowest DNA longevity. Conclusion: 1) Unnecessary incubation of spermatozoa prior to artificial insemination or in vitro fertilization, should be avoided, since sperm DNA longevity is significantly reduced after ex vivo sperm handling and 2) Although sperm selection by DCG significantly reduces the baseline levels of SDF of sperm in Fraction 3, sperm DNA longevity in this fraction was ultimately lower following 24 h incubation when compared to sperm recovered from non-centrifuged NSS.